Aging and Other Determinants on the Healthcare Burden: A Comparative Analysis of China, Indonesia, Malaysia, and Thailand - Chayutrakorn, Chalita; Tubpond, Ekkapol (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The Asia-Pacific region is undergoing a rapid demographic transition, with the population aged 60 and over projected to double from 630 million in 2020 to 1.3 billion by 2050. This shift presents significant challenges for healthcare systems in China, Indonesia, Malaysia, and Thailand, which face increasing pressure from aging populations, urbanization, and evolving socioeconomic conditions. This paper investigates how aging and other determinants contribute to increasing healthcare burdens in these four nations. It specifically examines the influence of demographic transitions on healthcare spending patterns and the effectiveness of respective financing reforms. The study utilizes a comparative analysis of empirical evidence regarding healthcare financing and policy reforms across the four countries. The theoretical framework incorporates the Health-Led Growth Hypothesis (HLGH), Willingness to Pay (WTP), and the relationship between permanent income and household healthcare expenditure. While each country has adopted unique reform strategies, common challenges persist regarding the rising healthcare burden caused by aging societies. Policymakers must prioritize innovative financing mechanisms and expand insurance coverage to ensure sustainable healthcare systems.